H HUBUNGAN PENGETAHUAN IBU PRIMIPARA DENGAN PEMBERIAN AIR SUSU IBU EKSKLUSIF DI WILAYAH KERJA POLI ANAK RSUD SULTAN SURIANSYAH BANJARMASIN - Muhsinin, Muhsinin; Permana, Subakta (Journal of Nursing Invention, 2023)
Background: The low achievement rate of exclusive breastfeeding certainly needs attention. The percentage of exclusive breastfeeding decreases every year in the South Kalimantan area, while the target is 80%, this is the task of nurses in providing education about the importance of exclusive breastfeeding, especially for primiparous mothers. Objective: This study aims to determine the relationship between knowledge of primiparous mothers and exclusive breastfeeding in the work area of the Pediatric Clinic of Sultan Suriansyah Hospital Banjarmasin. Methods: This study is a correlative study with a cross sectional approach. The population in this study were 120 primiparous mothers who brought their children to the pediatric clinic from January to August. The number of respondents was 92 people who were taken using the side purposive technique. The research instrument was a checklist sheet questionnaire of knowledge of primiparous mothers and exclusive breastfeeding. Statistical tests using spearman rank correlation. Results: Statistics showed 51 primiparous mothers (73.9%) were categorized as having insufficient knowledge and did not provide exclusive breastfeeding. Spearman rank correlation test obtained (p value = 0.000 < α = 0.05) which means there is a relationship between Primiparous Mother's Knowledge with exclusive breastfeeding at the Pediatric Clinic of Sultan Suriansyah Hospital, Banjarmasin City. Recommendation: It is hoped that this research can be an evaluation material to improve the quality of service at the Sultan Suriansyah Regional General Hospital, Banjarmasin City.